Creating a Standard of Practice for License Alternatives - Geuther, Christina M.; Greene, Mira E. (My University, 2016)
A gap exists in library literature for license alternative practices. Although licensing processes are a new concept, there is enough knowledge of best practices that will apply to alternatives. Much of the life cycle of electronic resources with and without licenses remains the same; therefore, a workflow can be framed for alternatives. Kansas State University created a standard workflow for managing license alternatives in its management systems Verde and Alma. We based this standard on the differences between licenses and their conventional alternatives, the NISO Shared Electronic Resource Understanding, and terms of use without registered or signed agreement. Aspects of this presentation will also apply to institutions without electronic resource management (ERM) systems. After considering the acquisition and review practices of license alternatives, a discussion of interlibrary loan as well as enforcing terms in the patron community will be offered. Interlibrary loan staff will easily interpret their procedures of fair use based on documentation in the ERM.
Citation: Geuther, Christina & Greene, Mira (2015). Creating a Standard of Practice for License Alternatives. In B.R. Bernhardt, B.R. Hinds, & K.P. Strauch (Eds.), Proceedings from Where Do We Go from Here? : Charleston Conference. West Lafayette, IN: Purdue University Press.
Keywords: Standard of Practice; Electronic Resource Management (ERM); Shared electronic Resource Understanding (SERU); Life Cycle; Licensing; Interlibrary Loan